Abelova nagrada 2009 Mikhaelu Gromovu - Forstnerič, Franc (Obzornik za matematiko in fiziko, 2010)
The article brings some basic facts on the life and work of the famous Norwegian mathematician Niels Henrik Abel, on the establishent of the Abel Prize, and on the revolutionary contributions of the 2009 Abel Prize winner, Mikhael Gromov, to geometry. The last part contains an exposition of the Oka-Grauert-Gromov principle in complex analysis and geometry.
Keywords: Abel, Niels Henrik; Abelova nagrada; biografije; Gromov, Mikhael; matematika; nagrade; Norveška